Analysis of Competitive Advantage Strategies to Expand Market Share - Ricki Adi Sanja; Survival; Mulyono (Journal of Management Research and Studies, 2025)
The increasingly tight business competition has made business people start competing to outperform their competitors in various ways, starting from offering the best quality products, the fastest service, a wide variety of products to conducting various promotions and providing attractive offers, some of these strategies will not be maximized if business people do not know in detail what consumers really want. The purpose of this study is to analyze the internal and external environment and formulate a competitive strategy formulation. Data collection using interviews and questionnaires. While for the analysis method using SWOT analysis and Porter's competitive strategy analysis consisting of the industrial competitive environment and generic strategies. From the results of the study, PT. Greenfields Indonesia has determined the Focus Strategy, where PT. Greenfields Indonesia concentrates on the regional market or special buyer groups. The focus of PT. Greenfields Indonesia's products focuses on pasteurized milk.